Public Private Partnership in the Provision of Health Services for the Millennium Development Goals: The Imperative Need for Optimizing the Public-Private Mix - Maximus N. O. Asogwa; Severus I. Odoziobodo (European Scientific Journal, ESJ, 2016)
Nigeria, with its large public sector, equally has an extensive wellestablished private sector; even with the ravages of the recent economic crisis. Both sectors play complementary and important roles as providers of expertise and as implementing agencies. Public-Private Partnership (PPP), the paper posits, is therefore an effort where the government of Nigeria provides the minimum standards required for coordinated collaboration with private sector, in the case of this study, the health sector. Notwithstanding various investment efforts from the public and private sectors into the Nigeria health economy, the performance of the national health system remains deplorable. The paper believes that the declining resource allocation to health, increasing costs and the breakdown in the public health facilities, make the achievement of health-related MDGs’, Millennium Development Goals’, (now SDGs, Sustainable Development Goals’) targets difficult. It is on the basis of this that the study, examines the pattern and scope of existing collaborations, including the nature, distribution of stakeholders in the sector and the characteristics of PPP in the health sector. It also examines the challenges, options and potentials for future partnership. These are examined within the strategic framework of MDGs and suggestions are made on how to overcome the challenges of public-private interventions to ensure effective policy interventions in the current Sustainable Development Goals, SDGs.